Exploring Mental Health Literacy Interventions: A Scoping Review and Future Directions - Raharjo, Alim Panggih; Munawaroh, Mudrika (Universitas Ahmad Dahlan, 2025)
Mental health issues are increasingly considered necessary by society. However, if it is not balanced with mental health literacy, individuals with mental disorders will find it difficult to heal and the stigma will be challenging to reduce. An intervention must be used to improve mental health literacy in the community. This study aims to discover mental health literacy interventions in various settings and recommendations for further research. This study was conducted using the scooping review method using the PRISMA-ScR guide. Ten studies were found from the SCOPUS, ScienceDirect, and SpringerLink databases. The results of the analysis found that various mental health literacy interventions were proven effective and could be implemented in school, community, worker, and family settings. Recommendations for further research are discussed in this study.